Importance of Friendship and Minimal Group Membership in 4-6-Year-olds' and 9-12-Year-olds' Sharing Behavior in China - Song, Yue; Shi, Yunqing; Huang, Yun; Zang, Fenglin (The Journal of genetic psychology, 2024)
Strategies for favoring close others, such as friends and in-group members, benefit individuals and society. Although younger and older children apply these sharing strategies, how they integrate these relationships remain understudied. Friendship and group membership sometimes conflict (e.g. a friend from another, even a rival group), driving the question of how children behave in such situations. To address this question, this preregistered study recruited 121 4-6-year-olds and 94 9-12-year-olds from a middle-class community in China. A 2 (friend vs. stranger) by 2 (in vs. out-group) between-subjects design was applied per age group. Participants were asked to share seven objects with a recipient, who was either a stranger, or a previously nominated friend and from an in- or out-group (manipulated in the Minimal Group Paradigm). The results showed that children in both age groups shared more with friends than with strangers. However, only 4-6-year-olds shared more resources with in-group members than with out-group ones. Moreover, 4-6-year-olds did not distinguish between an out-group friend and an in-group stranger, while 9-12-year-olds shared more with an out-group friend relative to an ingroup stranger, indicating that friendship outweighs minimal group membership only among 9-12-year-olds. Furthermore, there was an interaction between age and minimal group membership, implying a decrease in the minimal group effect between 4-6-year-olds and 9-12-year-olds. Accordingly, the implications of friendship and minimal group effects, and their relative influence on sharing during childhood are discussed.